KALIMAT TANYA DALAM FILM GODâ€™S NOT DEAD KARYA HAROLD CRONK - ,, Jessi; Kodong, Fentje; Ranuntu, Garryn Ch. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTThis research, entitled â€œThe Interrogative Sentence in the Film Godâ€™s Not Dead by Harold Cronkâ€, is aimed to identifying, classifying and analyzing the types of interrogative sentence found in the film. The data have been collected by downloading the movie and script of Godâ€™s Not Dead, observing the script by watching it directly, taking the data from the rerecorded and written data, taking notes whenever the interrogative sentence found and analyzing the data based on related theory. Interrogative sentence is a sentence consisting of a subject and in front of an auxiliary verb or Wh- question. Further explained that the question sentence beginning with an auxiliary verb is called a yes or no question and the other type of sentence consists of a question called tag question. The result shows that there are four forms of interrogative sentence in English used in the film. Those are yes/no interrogative, alternative interrogative, Wh- interrogative, tag question. Yes/no interrogative usually will be answered by yes or no, alternative interrogative offer two or more alternative responses, Wh- interrogative are introduced by Wh- word and they elicit an open ended response, tag question they are sometimes tagged onto the end of a declarative sentence.______________________Keywords: Interrogative Sentence, Grammatical Analysis, Film